Hydrogen engines as a building block of European energy autonomy: Acceptance factors and political decisions - J. Meitz; D. Faude; Lisa Strauch; V. I. Kämpf; Michaela Gläß; Ulrich Walther (OrdnungsPolitisches Portal (OPO), 2026)
The European Union has set forth an objective to reduce its reliance on fossil fuels and external supply chains. Hydrogen technologies are regarded as a pivotal element in achieving a sustainable and resilient energy supply. Despite the prioritization of hydrogen-powered fuel cells in numerous strategies, hydrogen combustion engines also offer promising opportunities, particularly with regard to heavy-duty applications and industrial processes. The successful deployment of this technology hinges upon its societal acceptance. The present paper analyzes, on the basis of empirical studies, the determinants influencing the acceptance of hydrogen engines in various societal and economic contexts. In doing so, it takes into account the political, infrastructural, and technological framework conditions. Additionally, the paper explores the potential contributions of the promotion of hydrogen engines to the European Union's strategic autonomy in the energy sector. Finally, policy recommendations have been formulated to support broader societal acceptance and the economic implementation of this technology.
Keywords: 330; Societal Acceptance; Energy Autonomy; European Union Policy; Decarbonization; Hydrogen Internal Combustion Engines